Visual impairment and rehabilitation sourcebook - 4 0 16; (Editor of health information), Hayes, Kevin; 5 (Detroit, MI : Omnigraphics, 2020)
Provides basic health information about visual impairment, its types and prevalence, conditions that lead to visual impairment, guidelines for people with visual impairment to lead a quality life, and facts about benefits and support services available for them. Includes resources for additional help and information--
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; Rehabilitation.;Services for. -- Vision disorders.;People with visual disabilities;People with visual disabilities -- 20; 20; 2